2012
DOI: 10.1016/j.neuron.2012.08.015
|View full text |Cite
|
Sign up to set email alerts
|

REM Sleep Reorganizes Hippocampal Excitability

Abstract: SUMMARY Sleep is composed of an alternating sequence of REM and non-REM episodes, but their respective roles are not known. We found that the overall firing rates of hippocampal CA1 neurons decreased across sleep concurrent with an increase in the recruitment of neuronal spiking to brief “ripple” episodes, resulting in a net increase in neural synchrony. Unexpectedly, within non-REM episodes, overall firing rates gradually increased together with a decrease in the recruitment of spiking to ripples. The rate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
311
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 295 publications
(344 citation statements)
references
References 43 publications
(75 reference statements)
31
311
1
1
Order By: Relevance
“…Specifically we first segregated the WAKE state from the two sleep states based on the 3-D accelerometer data. Next SWS and REM sleep stages were determined by the theta (5-10 Hz)/delta (1-5 Hz) ratio extracted from the power spectrum of the LFP from VC, according to generally accepted practice (Grosmark et al, 2012;de Lavilléon et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically we first segregated the WAKE state from the two sleep states based on the 3-D accelerometer data. Next SWS and REM sleep stages were determined by the theta (5-10 Hz)/delta (1-5 Hz) ratio extracted from the power spectrum of the LFP from VC, according to generally accepted practice (Grosmark et al, 2012;de Lavilléon et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, when a memory is being encoded indicating its importance for future use in a test appears to increase the likelihood of that memory being consolidated in sleep (Wilhelm et al 2011). Our understanding of specific memory functions and neurobiological processes in sleep is increasing, yet there remain many issues requiring further research (Chauvette, Seigneur, and Timofeev 2012;Grosmark et al 2012). …”
Section: Other Educational Considerationsmentioning
confidence: 99%
“…Vyazovskiy et al [37] also found that periods of neural silence are long and frequent during early non-REM sleep after prolonged wakefulness. On the other hand, Grosmark et al have also recently found that the alternating REM and non-REM episodes during sleep are characterized by different hippocampal excitability [38], implying a possible neuromodulation of firing in the sleep states. These observations are consistent with a scenario in which the homeostatic equilibrium of neurotransmitters is different between sleep states and the awaken state and could be mimicked by adjusting the values of these probabilities.…”
Section: A Cellular Automata Network Model Of the Brainmentioning
confidence: 99%